The Waqf Integrated Income-Generating Model: A Catalyst for Indonesia's Sustainable Development Ambitions - Haidar, Abdullah; Herindar, Evania; Arviannis, Tasya; Nursyamsiyah, Ikha; Hendrasto, Nur (EKONOMIKA SYARIAH : Journal of Economic Studies, 2024)
This research delves into the effect of collective beliefs and anticipations regarding investment cooperation, technological progression, and administrative governance on fostering sustainable income through the Waqf Integrated Income Generating Model (WIIGM). The study, grounded in the Theory of Reasoned Action (TRA), empirically assesses public perceptions of the WIIGM. A survey conducted among 100 participants through convenience sampling and online questionnaires provides the data, which is analyzed using partial least squares structural equation modeling to test hypotheses. Prior ethical approval was secured for data collection. Findings from this study highlight that sustainable income is positively influenced by investment collaboration and governance, but not by technological advancements. In terms of building trust (behavioral intention) in the WIIGM model, technological advancement does not show a significant effect. This novel investigation offers insights into how a newly proposed integrated income model for waqf institutions could enhance community trust. The study holds substantial implications. It is intended for professionals and government officials to understand waqf's functions, positions, and potential applications, considering community trust and beliefs.